Optimization of a fermented soy product formulation with a kefir culture and fiber using a simplex-centroid mixture design. (22nd July 2013) - Baú, Tahis Regina; Garcia, Sandra; Ida, Elza Iouko
Abstract: The objective of this work was to optimize a fermented soy product formulation with kefir and soy, oat and wheat fibers and to evaluate the fiber and product characteristics. A simplex-centroid mixture design was used for the optimization. Soymilk, soy, oat and wheat fiber mixtures, sucrose and anti-foaming agent were used for the formulation, followed by thermal treatment, cooling and the addition of flavoring. Fermentation was performed at 25 °C with a kefir culture until a pH of 4.5 was obtained. The products were cooled, homogenized and stored for analysis. From the mathematical models and variables response surface and desirability an optimal fermented product was formulated containing 3% (w/w) soy fiber. Compared with the other formulations, soy fermented product with 3% soy fiber had the best acidity, viscosity, syneresis, firmness and Lactococcus lactis count.